The Legal Dimension of the Formation and Function of the Hellenic Supremes Councils for Marine Accidents - Tryfon Ch. Korontzis (European Scientific Journal, ESJ, 2023)
Shipping is perhaps the largest industry globally, transporting more than 90% of the world's trade efficiently and safely. Ships, given their activity on a global scale, are subject to different legal regimes. However, marine accidents with adverse consequences for the environment and people still occur. Hellas, as a country with a strong maritime tradition and with one of the largest shipping companies in the world since the 70s, has established a special legislative framework for the investigation of marine accidents with the Act Decree (A.D.) 712/1970 (A΄ 237). This special legislative process will be critically examined in this brief study.